Agenda comunitaria para la protección de páramos y bosques nativos en la comunidad de Salamalag chico, parroquia Guangaje, cantón Pujilí, provincia de Cotopaxi, 2022. - Chicaiza Chacha, Sandy Pamela (2022)
The research project was developed in the community of Salamalag Chico in the Canton Pujilí, Province of Cotopaxi, the general objective is based on developing a community agenda for the protection of the paramo and native forest of the community of Salamalag Chico, it is broken down into three important specific objectives that is to diagnose the problem of the páramo, identify the socio-environmental scenarios and the design of the community agenda. For this reason, the research was carried out through the mixed method, which allowed determining qualitative and quantitative conditions, in which instruments such as GPS were used to determine the geographical coordinates of the area, surveys to be able to identify socio-environmental scenarios, their environment and the interviews to find out the deterioration that the moor is going through today; thus, the Andean Community Planning (PAC) method was also implemented, for the development of the agenda, techniques such as participatory workshops with environmental, social, cultural and economic aspects were applied. The main results showed that the population consists of 878 inhabitants in the respective study area, in the same way through the surveys it was determined that there are health, mortality and education problems, it was also possible to identify that the Provincial Council is in charge of preserving the páramo as an environmental protection zone, of course the páramo was also determined as a source of income for livestock, sheep and guinea pig production, it should be emphasized that the main sources of income are the agriculture of onions, potatoes, broad beans and mellocos; In addition to the sale of animals. Regarding the community agenda, topics were implemented on: the axis of water resources, climate change, biodiversity and cultural, social and economic issues, to provide knowledge to the community about ideas of conservation to the moor and to promote tourism, giving socio-environmental and economic actions as a priority. Concluding with this investigation, it was determined that ecotourism will become a tool to take advantage of the landscape and biodiversity.